Peningkatan Pengetahuan Tentang Infeksi Kecacingan Pada Anak Sekolah Dasar - Yuliana Yuliana; Suriyani Tan; Jipri Suyanto; Machrumnizar Machrumnizar (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Infestation with intestinal worms is a disease caused by parasitic worms, transmitted through the eggs present in the feces of infected individuals and contaminating the soil in environments with poor sanitation. It is estimated that around 1.5 billion people, or approximately 24% of the world's population, are affected by this disease. In Indonesia alone, there were 73,108,392 preschool and school-age children requiring preventive treatment for worm infestations in 2021. Worm infections are often overlooked due to the indirect nature of their effects, even though they can lead to long-term consequences, especially for young children, predominantly those in preschool and school-age. Preventive treatment measures implemented in Indonesia involve administering large-scale anthelmintic drugs to at-risk populations, which can reduce the number of worms infecting individuals. This intervention has the potential to decrease the morbidity associated with severe worm infestations. Furthermore, preventive measures to lower the prevalence of worm infections include educational campaigns on preventing worm infestations. With adequate knowledge of prevention methods, then communities can take steps to prevent the spread of these worm infections.